Principles for determination of size of structural elements of object of the scanned image - Колесникова, Татьяна Анатольевна; Жук, Екатерина Юрьевна; Федько, Юлия Игоревна (Eastern-European Journal of Enterprise Technologies, 2012)
The algorithm for estimating the size of the basic structural elements of the scanned digital images, which is based on calculating the length of runs, is investigated in this work. The analytical and practical results of research are presented, the inspection of the effectiveness of the proposed algorithm is made